Year‐round distribution suggests spatial segregation of two small petrel species in the South Atlantic. (16th November 2012) - Quillfeldt, Petra; Masello, Juan F.; Navarro, Joan; Phillips, Richard A.; Araújo, Miguel
Abstract Aim Pelagic seabirds exploit large areas of ocean when acting as central‐place foragers during the breeding season, and ranges are even more extensive outside the breeding period. Spatial niche partitioning is known to occur among species that breed sympatrically, but is less apparent during the non‐breeding period when there is increased potential for overlap among closely related species from neighbouring island groups. This applies to several species of prion, Pachyptila spp., in the Southern Ocean; although extremely abundant, their at‐sea distribution was virtually unknown because they are difficult to distinguish while at sea. To understand spatial niche partitioning at large scales, we investigated the year‐round distribution of thin‐billed prions (Pachyptila belcheri) from the Falkland Islands (Islas Malvinas) and Antarctic prions (Pachyptila desolata) from South Georgia. Location South Atlantic Ocean. Methods Recently, geolocation devices have become small enough to be deployed on small seabirds. During 2009–10, we tracked 20 thin‐billed prions and 9 Antarctic prions with miniaturized geolocators. We applied ecological niche models to compare environmental conditions in the habitat utilized year‐round. Results We show that two prion species from the south‐west Atlantic Ocean have divergent patterns of migration, and that this has resulted in nearly complete spatial segregation (0–5% overlap by month in the 95% kernel density polygons). Nineteen of 20 thin‐billed prions migrated to an area > 3000 km east of their breeding site, whereas all Antarctic prions migrated a much shorter distance, and to the north‐west. The non‐breeding distribution of thin‐billed prions included the waters around South Georgia, but only when the Antarctic prions were absent. The models highlighted large differences in the realized niche between the two species, and between the habitat characteristics of breeding and non‐breeding areas of thin‐billed and Antarctic prions. Main conclusions Our results are consistent with the prediction that spatial niche partitioning occurs at large scales, allowing the co‐existence of related species. The methods applied here will enable predictive maps of the distributions of other prion populations to be created, once data become available from other breeding sites in the Southern Ocean.